If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6b + -5a = 4 Reorder the terms: -5a + 6b = 4 Solving -5a + 6b = 4 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-6b' to each side of the equation. -5a + 6b + -6b = 4 + -6b Combine like terms: 6b + -6b = 0 -5a + 0 = 4 + -6b -5a = 4 + -6b Divide each side by '-5'. a = -0.8 + 1.2b Simplifying a = -0.8 + 1.2b
| f(x)=-3x^2+2x+4 | | 7p+2q=-5 | | 4xln(x)=0 | | 2t+11=34 | | 4s=29 | | x^3-2.25x^2=-3.25 | | 252-9n=170 | | 20-120/7 | | -33=3x+-6 | | 2y+4x=11yequal | | 252-9n=168 | | 13x-5=4x-9 | | n*1.5*6=28-n*0.5*6 | | 3n+9n=28 | | ax-3x=4 | | N=28-3 | | -v+5+6v=1+5v+3 | | 3p+6=11p-1 | | 7777=8 | | 1+4y=17 | | 2(x-7)=6(-9) | | 6q-26=50-1/3q | | 32x^3+36x^2-4=0 | | 933=(10x-150)*ln(2x-29) | | 2x/12x^2 | | 9(x-7)=2(5x+7) | | -2sin[3(x-180/4)] | | x^2+2y^2=99 | | x^3-12x+10=10-3x | | 15x+7y=25 | | x/4-4x/7=2 | | .5(a+6)3=15 |